2010
DOI: 10.1007/s11239-010-0520-2
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for haemorrhage during local intra-arterial thrombolysis for lower limb ischaemia

Abstract: Assessment of clinical risk factors for haemorrhagic complications in patients undergoing intra-arterial thrombolysis for lower limb ischaemia. Retrospective reviews of consecutive patients subjected to intra-arterial thrombolysis due to lower limb ischemia at the Vascular Center, Malmö University Hospital, during a 5-year period from 2001 to 2005. Two hundred and twenty intra-arterial thrombolytic procedures were carried out in 195 patients (46% women), median age 73 years. Haemorrhagic complications were rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 18 publications
0
14
1
Order By: Relevance
“…Conrad et al, on the other hand, suggested repeat operation with a completely new bypass graft as a more appropriate option due to poor short-term results of thrombolysis of occluded prosthetic grafts. 15 In contrast with previous findings, 16 this patient series did not exhibit an increased risk of major hemorrhagic complications after thrombolysis of synthetic grafts.…”
Section: Discussioncontrasting
confidence: 95%
“…Conrad et al, on the other hand, suggested repeat operation with a completely new bypass graft as a more appropriate option due to poor short-term results of thrombolysis of occluded prosthetic grafts. 15 In contrast with previous findings, 16 this patient series did not exhibit an increased risk of major hemorrhagic complications after thrombolysis of synthetic grafts.…”
Section: Discussioncontrasting
confidence: 95%
“…13 Hence, the fear of fatal or life-threatening gastrointestinal hemorrhage during thrombolysis seems to be unfounded and might be exaggerated. In the absence of acute peritonitis, the risk of bleeding complications [14][15][16] should not deter the clinician to go ahead with thrombolysis for the treatment of this life-threatening condition. If needed, early explorative laparotomy can be performed after discontinuation of thrombolysis and reversal of heparin with protamine.…”
Section: Discussionmentioning
confidence: 99%
“…In case of severe bleeding, there is no need of reversal of alteplase after thrombolysis is stopped because it has a short duration of effect and a negligible effect on coagulation factors, whereas reversal of heparin is mandatory. 16 A detailed analysis of the relaparotomies showed that these procedures mostly were performed on-demand due to unsuccessful endovascular intestinal revascularization or development of bowel infarction, or both, and were associated with high mortality. Hence, few patients underwent a planned routine second-look relaparotomy.…”
Section: Discussionmentioning
confidence: 99%
“…A higher dose of rtPA can accelerate the thrombolysis and achieve faster restoration of blood flow, a potential advantage to patients with acute ischaemia14,25,26. Faster thrombolysis with a higher dose of rtPA is counterbalanced by a higher rate of bleeding complications16,25; the risk of bleeding must be weighed against the risk of surgery or amputation for each patient27. The two hospitals in the present study used significantly different amounts of rtPA, but had equivalent success rates.…”
Section: Discussionmentioning
confidence: 83%
“…A recent study of thrombolytic procedures at Malmö University Hospital, Sweden, recorded a high rate of bleeding complications (33 per cent)15,16. At Uppsala University Hospital, Sweden, a different treatment algorithm was used during the thrombolytic procedure, with lower doses of both heparin and rtPA.…”
Section: Introductionmentioning
confidence: 99%